ASSOCIATION OF ADVERSE CHILDHOOD EXPERIENCES AND HEALTH RISK BEHAVIORS AMONG HIGH SCHOOL STUDENTS IN HUE CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe health-risk behaviors and examine the associations between adverse childhood experiences and other related factors with health-risk behaviors among high school students in Hue city.Subjects and methods: A cross-sectional study was conducted on 1112 high school students in Hue city in 2025. Health-risk behaviors were assessed using selected questions from the Global School-based Student Health Survey (GSHS). Data were collected through self-administered questionnaires. Multivariate logistic regression analysis was performed to identify factors associated with health-risk behaviors (p < 0.05).Results: The prevalence of high school students engaging in health-risk behaviors was 29.5%, of which 6.5% used traditional tobacco, 7.6% used electronic cigarettes, 27.0% consumed alcohol, and 0.3% had used stimulants. Multivariate logistic regression analysis revealed that the factors associated with health-risk behaviors among high school students included: type of school, current living situation, parental marital status, average monthly expenditure, exposure to e-cigarettes in the school environment, exposure to alcohol in the school environment, exposure to alcohol within the family/relatives, exposure to stimulants in the school environment, and adverse childhood experiences (p < 0.05).Conclusion: The prevalence of health-risk behaviors among students is relatively high. Therefore, it is necessary to strengthen health education and communication activities within schools, promote close coordination between schools, families, and society, enhance knowledge counseling and support services for students through media channels, and encourage students to raise their awareness and actively seek support to prevent engagement in health-risk behaviors.
Keywords: Adverse childhood experiences, health-risk behaviors, high school students.